Pars Plana Vitrectomy Reoperations for Complications of Proliferative Diabetic Retinopathy - Al-khersan H (Dove Medical Press, 2020)
Hasenin Al-khersan, Michael J Venincasa, Amy Kloosterboer, Jayanth Sridhar, William E Smiddy, Justin H Townsend, Harry W Flynn Department of Ophthalmology, Bascom Palmer Eye Institute, University of Miami Miller School of Medicine, Miami, FL, USACorrespondence: Harry W FlynnBascom Palmer Eye Institute, University of Miami Miller School of Medicine, Miami, FL, USATel +1 305-326-600Email HFlynn@med.miami.eduObjective: To report visual acuity in patients undergoing pars plana vitrectomy (PPV) reoperations for complications of proliferative diabetic retinopathy (PDR).Design: Retrospective case series.Subjects: Diabetic patients undergoing reoperation with PPV between 2015 and 2018 at a university referral center.Methods: Patient charts were reviewed for indication for initial and repeat PPV, baseline clinical characteristics including gender, age, and lens status, and pre- and post-operative best-corrected visual acuity.Main Outcome Measures: Best-corrected visual acuity at last follow-up.Results: Of 538 eyes (409 patients) undergoing a PPV for diabetic retinopathy, 153 (28.4%) eyes had reoperation. Among the 130 eyes (119 patients) that met the inclusion criteria, 55 eyes (50 patients) underwent reoperation for complications of PDR, defined as non-clearing vitreous hemorrhage (NCVH) and/or tractional retinal detachment (TRD). Within this subgroup of 55 eyes, 19 (34.5%) eyes had an indication for the first surgery of NCVH. Fourteen (73.7%) of these NCVH eyes achieved a visual acuity of 20/80 or better. When the indication for the first surgery was TRD (33 eyes, 60%), 8 (24.2%) eyes achieved this same outcome (p=0.0011).Conclusion: Approximately one of every four eyes treated with PPV for PDR will undergo repeat PPV during follow-up. VA outcomes after the repeat PPV were variable, with NCVH cases achieving better outcomes compared to TRD.Keywords: vitreoretinal surgery, diabetic retinopathy, retinal detachment, retina